PERAN CORPORATE GOVERNANCE DAN LEVERAGE TERHADAP RISK DISCLOSURE PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ferlisa Septania Menawati, 11.05.52.0068; Suwarti, Titiek (Students Journal of Accounting and Banking, 2015)
This research was conducted to test the effect of corporate governance to risk disclosure of banks firms. Corporate governance are identified as the Board Size, The Proportion of Independent Director, The Proportion of Woman Director, The Educational Background of Director, The Culture Background of Director, The Number of Board Meetings, The Number of Audit Committee Meetings, The Proportion of Independen Audit Committee Members and Leverage.The population used in this study is the Banking Company listed in Indonesia Stock Exchange ( IDX ) during 2011-2013. Sampling method used is purposive sampling, with a total sample of 94 and 34 companies that meet the criteria. The test results showed that the variable The Board Size, The Number of Audit Committee Meetings, and The Proportion of Independen Audit Committee Memberspositive and significant on the Risk Disclosure. The Proportion of Independent Director, The Educational Background of Director, and The Number of Board Meetings negative no significant on the Risk Disclosure. The Proportion of Woman Director, and The Culture Background of Directorpositive and no significant on the Risk Disclosure. And LeverageÂ negative and a significant on the Risk Disclosure.Keywords: Corporate Governance, Leverage, Risk Disclosure